Pembuatan Posyandu Latsitarda Nusantara ke-XLIV/202 Pada Masyarakat Pinggir Sungai Mahakam Balikpapan - Mardamsyah, Adam; Saragih, Hondor; Rachman, Arif; Pannyiwi, Rahmat (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Posyandu is a form of community-based health effort. Therefore, to provide excellent Posyandu health services for mothers, children and the community, various facilities, infrastructure and adequate environmental sanitation are very necessary. Therefore, the Dansatgas of the Indonesian Defense University, Colonel Inf, Adam Mardamsyah, M.Han in the implementation of the XLIV/202nd Latsitarda Nusantara activities has called for the creation of posyandu for health services for the community in carrying out Clean and Healthy Living Behavior so that they get health services, especially for households that have toddlers, breastfeeding mothers and pregnant women and play an active role in health activities. The aim of this PkM activity is to establish posyandu services in an effort to improve public health and increase community participation in the health sector, especially communities who live around the Mahakam river. The method for implementing this Community Service Program is the creation of a posyandu which was carried out by the Indonesian Defense University Task Force together with the Yonsatlak-2/Hiu Team in an effort to develop the use of posyandu land. The result of the activity was the formation of the XLIV/202nd Posyandu Latsitarda Nusantara for the community to provide health services in their environment. The conclusion of this activity is the formation of the Latsitarda Nusantara posyandu service, which is one of the community's efforts to obtain health services, especially households with toddlers, breastfeeding mothers and pregnant women. So that it has an impact on efforts to improve public health and increase community participation in the health sector in implementing clean and healthy living behavior.